CRITERIA ANALYSIS FOR TRUCK HD465-7 AS A GUIDELINE FOR SAFETY MINE HAUL ROAD DESIGN. - Nur Ramadhan, Zakiy
Indonesia has a huge potential for mining. To ensure the transport process can work well not only takes a good means of transport, but also needed a safe path and provides good stability to the vehicle transporting mining products, as well when going uphill, downhill, and cornering. This final project analyses mining trucks criteria for trucks that are widely used in mining Indonesia, the truck HD465-7. The truck dimensions 9.3m x 4.5m x 4.6m with a maximum speed of 70 km / h has a payload capacity of 55 tons. The analysis begins by calculating the width of the straight road and curve roads from truck outer dimensions. Then determine the minimum curve radius for the operating speed of 20km/hr to 70km/hr on the friction coefficient from 0.1 to 0.9. From the specified radius can be used to calculate stopping distance, minimum length of the hill, and the middle-ordinate. The results of the calculations are presented in tables for easy viewing. Based on the analysis, obtained straight road 16m wide and 30m for curves. Vertical curves (hills) can use the operating speed of 50km/hr on the super-elevation of 8% - 10% and 60km/hr in 5% - 10% as a reference. Horizontal curves can use the operating speed of 20km/hr - 70km/hr.